The Effect of Environmental Factors on Conidial Germination, Sporulation and Growth of Trichoderma harzianum In Vitro - Arif Wibowo (Jurnal Perlindungan Tanaman Indonesia, 1999)
This experiment was conducted to study the influence of temperature, pH of media, and length of radiaton on conidial germination, sporulation and growth of Trichoderma harzianum on PDA (Potato Dextrose Agar). It was conducted in a Completely Randomized Design (CRD) with 3 replications. The results indicated that the highest conidial germination occurred at 30°C, and so the sporulation and the growth of T. harzianum. Length of radiation did not significantly affect conidial germination. However sporulation was enhanced by 12 hrs light-12 hrs dark treatment and colony diameter of T. harzianum was significantly greater at dark. Acidity influenced mainly the conidial germination and the sporulation of T. harzianum. The greatest of conidial germination occurred at pH 8, whereas the smallest occurred at pH 5. Sporulation was also enhanced by higher pH. The influence of acidity on the growth of T. harzianum occurred at pH 9 which its diameter colony was significantly smaller compared to the other treatments.